Impelementasi Kurikulum Merdeka Belajar Pada Pembelajaran Projek Penguatan Profil Pelajar Pancasila di SMP IT Ar-Ridha Pantai Cermin - Siti Wahyuni; Hayatun Sabariah (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study aims to examine the application of the concept of Merdeka Belajar through Pancasila Profile students in learning Islamic Religious Education (PAI) at Ar Ridha Pantai Cermin IT Junior High School. The research uses descriptive qualitative method to deeply understand the dynamics of learning in the field. Data are collected through observation, interviews, and document analysis related to the learning process. The results showed that the implementation of Merdeka Belajar creates a pleasant learning environment, with learning that favours students and the use of varied methods by PAI teachers tailored to student needs. Teachers at SMP IT Ar Ridha Pantai Cermin also emphasise the importance of noble moral values, global diversity, mutual cooperation, independence, critical reasoning, and creativity in accordance with the Pancasila Learner Profile. The obstacles faced include the lack of socialisation and training from the education office and the lack of technical guidance related to the preparation of the Merdeka Curriculum teaching module, most of which information is conveyed through WhatsApp groups based on the Ministry of Education and Culture's circular letter.